Subcutaneous Administration of Melatonin Resumes the Cyclicity and Improves Conception Rate in Anestrus Buffalo Heifers - Chaudhari, Ravjibhai K.; Sutaria, Tarunkumar V.; Patel, Mayank P.; Chaudhari, Chandrakant F. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was aimed to see the effect of subcutaneous injection of melatonin @ 18 mg/50 kg b.wt. on estrus induction and conception rate in anestrus buffalo heifers (n=24). Among the heifers treated with melatonin (n=14), 6 (42.86 %) animals showed behavioral estrus within 4-28 days of treatment as compared to none in control group (n=10). The first service conception rate was 33.33 % (2/6) in the melatonin treated buffaloes, while none of the buffalo exhibited estrus/conceived in control group. It is concluded that melatonin @ 18 mg/50 kg b.wt. can be used to induce the estrus in anestrus buffalo heifers with satisfactory conception rate.